2022
DOI: 10.1007/s40256-022-00524-x
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban Use in Obese Patients: A Review of the Pharmacokinetic, Interventional, and Observational Study Data

Abstract: Relatively little is known about the influence of extreme body weight on the pharmacokinetics (PK), pharmacodynamics (PD), efficacy, and safety of drugs used in many disease states. While direct oral anticoagulants (DOACs) have an advantage over warfarin in that they do not require routine drug monitoring, some may regard this convenience as less compelling in obese patients. Some consensus guidelines discourage using DOACs in patients weighing > 120 kg or with a body mass index > 35–40 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Specifically, other observational studies and randomised controlled trials (RCTs) widely suggest that increased BMI in VTE/NVAF has no significant effect on the safety and efficacy of apixaban. In other words, despite exposure being slightly reduced, no dose adjustment was required [20]. However, this does not dismiss the claim that the morbidly obese category had the most incidence of thrombotic events among the BMI classes [8,9,21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, other observational studies and randomised controlled trials (RCTs) widely suggest that increased BMI in VTE/NVAF has no significant effect on the safety and efficacy of apixaban. In other words, despite exposure being slightly reduced, no dose adjustment was required [20]. However, this does not dismiss the claim that the morbidly obese category had the most incidence of thrombotic events among the BMI classes [8,9,21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Patients are primarily older than 65, with decreased renal function and other comorbidities [ 13 , 14 ]. Nevertheless, recent studies suggested that age, gender, and obesity do not have a clinically relevant effect on the pharmacokinetics and pharmacodynamics of FXa inhibitors [ 15 , 16 ]. Furthermore, the influence of renal function on clearance of FXa inhibitors is moderate [ 17 , 18 ], even in subjects with severe renal impairment (creatinine clearance < 30 mL/min) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is disagreement in pharmacokinetic reports of DOAC peak and trough plasma concentrations when comparing normal and obese adults [17][18][19][20]. This disagreement pervades opinion regarding the clinical effect of obesity in the context of DOACs, given the lack of longterm outcome data and variability in prescribing [21,22].…”
Section: Introductionmentioning
confidence: 99%